The attempted synthesis of teucrolivin A via the oxy-CopeClaisenene reaction: Diastereoselective formation of quaternary centers directed by macrocyclic conformation and its application to the formal synthesis of (-)-mesembrine - Arns, Steve (University of Ottawa (Canada), 2008)
This thesis is the account of a journey through the world of total synthesis. It is a story of our attempts to tackle some of the persistent challenges faced by the synthetic chemist, showcasing our solutions through total synthesis. These issues include the rapid generation of complex molecules with high selectivity, and the stereoselective generation of quaternary centers. Out initial efforts were focused on the application of the oxy-Cope/Claisen/ene reaction towards the total synthesis of the natural product teucrolivin A. A route was developed to give access to advanced intermediates required for its synthesis. However the existing methodology did not fully accommodate the complete core structure of the target. This prompted an in-depth examination of the oxy-Cope/Claisen/ene reaction with a new class of substrate. From this study were able to gain insight into the use of this tandem reaction with sterically demanding substrates and we were able to assess the applicability of these substrates for use in the synthesis of teucrolivin A. Shifting gears, we developed an anionic oxy-Cope/alkylation sequence by which to generate all-carbon quaternary centers. This methodology exhibited high diastereoselectivity, where the selectivity was governed by the conformational preferences of a macrocycle in which an enolate generated from the anionic oxy-Cope rearrangement was embedded. Finally we applied this new procedure for the generation of quaternary carbon centers to the formal synthesis of the alkaloid natural product (-)-mesembrine.
Keywords: Chemistry, Organic.